An account of the Lentibulariaceae of Thailand - Parnell, J.A.N. (Thai Forest Bulletin (Botany), 2014)
The Lentibulariaceae of Thailand is represented by one genus, Utricularia, with 22 native species, following revision of Thai and associated materials. One new species is described: it is endemic to Thailand. Two additional species, U. stellaris and U. pierrei are included in the account as they are likely to be present in Thailand, though specimens of the former appear not to have yet been collected and records for the latter are uncertain. Field experience suggests that many Utricularia species remain poorly known in Thailand. As the number of collections of Lentibulariaceae housed in herbaria are generally relatively few the distributional data given are, necessarily, incomplete.